THE DANGER OF ANESTESIA DRUGS - M. Rahimi; D. Atashband (Tehran University of Medical Sciences, 1974)
Statistics have shown that the incidence of miscarriage among nurse anesthetists and anesthesiologists who were pregnant before being employed was 10% while those who were pregnant during their employment were 20%. This was attributed to the teratogenic effect of anesthetics agents used in the operating room on the fetus. Today with the use of special Askrog valve, 90% of the anesthetic gases could be directed out of the operating room, considerably reducing their dangers.